SCIENTIFIC AND METHODICAL BASIS OF ORGANIZATION AND TEACHING OF DRAWING LESSONS IN GENERAL SECONDARY SCHOOLS - Sobirova, Sh.U.; Badiev, M.M.; Shukurov, A.R.; Aminov, A.Sh. (The journal of contemporary issues in business and government, 2021)
It was shown that at different stages of drawing training not only the application of knowledge to new conditions, but also the solution of the initial state of the graphic material with a high degree of replacement is an important condition for the development of graphic thinking.